Determination of a willingness-to-pay threshold and decision-making in financing the healthcare technologies - T. S. Teptsova; T. P. Bezdenezhnyh; V. K. Fedyaeva; N. Z Musina; G. R. Hachatryan; V. V. Tarasov (Фармакоэкономика)
The aim was to develop a methodology for determining the willingness to pay threshold (WTPT) and its upper limit value within the Russian health care system.Materials and methods. WTPT was calculated based on the shadow budget price (i. e. determining the WTPT by the suppling party). This method is an empirical assessment of the cost-effectiveness threshold that reflects the utmost productivity of the health care system, as determined from the relationship between changes in healthcare expenditure and health outcomes achieved. The state’s willingness to pay for improving their citizens’ healthcare was evaluated considering the population of the Russian Federation, mortality and life expectancy in different age and gender groups, as well as the volume of government spending. The cost of disability-adjusted life-year prevented (DALY) and the cost of quality-adjusted life-year saved (QALY) were determined by the suppling party, that is, they reflect the cost the state is willing to pay for improving the health of their population under conditions of limited budget. The described approach considers the performance of the country’s healthcare system over a certain period and the costs incurred in functioning of the system.Results. As part of this study, it was found that the cost of one additionally prevented DALY would be 313,878.21 rubles, and the cost of one additionally saved QALY – 365,060.31 rubles.Conclusion. The WTPT for medical technologies in the Russian Federation, determined by estimating the shadow budget price will amount to 313,878.21 rubles for one prevented DALY and 365 060,31 rubles for one saved QALY. With regard to clinical and economic analysis, medical technologies with the incremental cost-effectiveness indicator not exceeding the one calculated in this study can be seen as cost-effective. The obtained threshold value is a recommendation. A medical technology can be approved even with a WTPT higher than the recommended level, because this specific technology may have additional  advantages other than WTPT when compared with the reference technologies.